2000
DOI: 10.1152/ajpheart.2000.278.3.h818
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure alters the strength and mechanisms of the muscle metaboreflex

Abstract: Heart failure alters the strength and mechanisms of the muscle metaboreflex. Am. J. Physiol. Heart Circ. Physiol. 278: H818-H828, 2000.-We hypothesized that excessive sympathoactivation observed during strenuous exercise in subjects with heart failure (HF) may result from tonic activation of the muscle metaboreflex (MMR) via hypoperfusion of active skeletal muscle. We studied MMR responses in dogs during treadmill exercise by graded reduction of terminal aortic blood flow (TAQ) before and after induction of HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
176
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(204 citation statements)
references
References 31 publications
23
176
2
1
Order By: Relevance
“…This suggests that humans rely on local vasodilator mechanisms, and not a reflex increase in pressure, to restore blood flow to hypoperfused contracting muscle. In contrast, there is overwhelming evidence that suggests a pressor response is essential in the restoration of blood flow to underperfused hindlimbs of exercising dogs (12,22,23,30,35). The discrepant findings between our series of studies in humans and those performed in dogs may simply be related to species differences.…”
Section: Restoration Of Flow Via Local Vasodilator Mechanismscontrasting
confidence: 58%
“…This suggests that humans rely on local vasodilator mechanisms, and not a reflex increase in pressure, to restore blood flow to hypoperfused contracting muscle. In contrast, there is overwhelming evidence that suggests a pressor response is essential in the restoration of blood flow to underperfused hindlimbs of exercising dogs (12,22,23,30,35). The discrepant findings between our series of studies in humans and those performed in dogs may simply be related to species differences.…”
Section: Restoration Of Flow Via Local Vasodilator Mechanismscontrasting
confidence: 58%
“…No exercise was performed in that study. Previous studies from our laboratory (11,12) have shown that in pacing-induced HF dogs, when MMR was activated during mild to moderate dynamic exercise, the increase in CO was significantly attenuated and the pressor response was more dependent on responses within the peripheral vasculature that result from increases in sympathetic outflow as well as the secretion of vasoactive hormones. In the present study after the induction of HF, we observed that SV and end-systolic pressure decreased.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, in normal dogs, MMR activation causes substantial central blood volume mobilization (35), which maintains ventricular filling pressure that would otherwise decrease due to the rise in CO (43,45). In HF, this central blood volume mobilization still occurs, as evidenced by large increases in central venous pressure (11), but evidently even this increase in filling pressure is ineffective in raising CO during MMR activation. Prabhu and Freeman (38) reported that alteration of lengthdependent activation is a fundamental defect in the development and progression in HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the right ventricular pacing electrodes were connected to an external pacemaker set at 240 -250 beats/min for ϳ30 days. After an induction of modest HF (defined as resting tachycardia, reduced CO, SV, and maximum and minimum first derivative of left ventricular pressure) as described in our previous studies (8,9,14,28), the experiments were repeated. The pacemaker was turned off before each experiment, and data collection began after the hemodynamic variables had reached steady state (ϳ30 min).…”
Section: Methodsmentioning
confidence: 99%